Kepemimpinan Wanita Kristen: Pengaruh Dan Tantangan Dalam Konteks Gereja Modern - Sedihati Bu’ulolo; Riste Tioma (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
In the context of the modern church, the leadership role of Christian women has become an increasingly important and complex issue. Despite increasing awareness of the importance of gender equality, there are still challenges and obstacles that hinder the advancement of Christian women in ecclesiastical leadership roles. This article aims to explore the influences and challenges faced by Christian women in ecclesiastical leadership and find solutions to promote their role in the modern church. Therefore, in this study the authors used a qualitative approach by applying a literature review and reflective analysis. A literature review was conducted to gather relevant literature on Christian women's leadership in the modern church, including scholarly articles, books, ecclesiastical journals, and theological sources. Reflective analysis was then carried out to deeply understand the influence that Christian women have on ecclesiastical leadership as well as to identify the challenges they face in the context of the modern church. Based on the literature review and reflective analysis conducted, this article reveals that Christian women have a significant influence in ecclesiastical leadership, including in ecclesiastical decision-making, public service, teaching, and spiritual guidance. However, they also face challenges such as restricted traditional roles, different interpretations of the Bible, gender stereotypes, lack of necessary support and training, and cultural conservatism. Therefore, this article concludes the need to recognize and promote the role of Christian women in ecclesiastical leadership by creating an inclusive environment, providing adequate training, overcoming cultural barriers, and promoting gender equality in the modern church.